Payment in heaven: Can early childhood education policies help women too?. Issue 1 (January 2018) - Newberry, Jan; Marpinjun, Sri
Based on research and activism on early childhood education and care in the area of Yogyakarta, Indonesia, we argue that the Indonesian government's focus on early childhood has come at a cost to local women. Community-based early childhood programs are delivered by women whose work is unpaid or underpaid. Although early childhood education in the form of kindergarten has long existed in Indonesia, its extension to the very young through Pendidikan Anak Usia Dini or early childhood education programs for children aged 0–8 years is more recent. Yet, there are many contradictions in this attention to the very young child. While the programs are designed to empower young children and improve their chances of success in education, the community-based programs promoted by the government are delivered through the work of women who may be denied these same benefits. Based on our separate researches, local women offer their services in early childhood education for a variety of reasons: they believe in these programs, they feel pressured to support their communities, or they desire to improve their own chances, and often all three. Yet, the opportunity to gain more education and to become a certified teacher is extremely limited for these women. As a result, they are trapped in unskilled, low, or no-waged work. While this contradiction can be described as a result of neoliberal policy, it has been the long-standing practice of the Indonesian state to depend on women's "volunteered" labor to deliver social service programming. Here, we challenge whether this is "neoliberal" policy or just a continued disregard for the value of the care labor in social reproduction and the simultaneous relegation of women to the "informal" sphere. We ask, what kind of policy options exist for linking the improvement of children's education and women's education simultaneously?